2010
DOI: 10.1016/j.ejps.2010.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Microemulsion formulations for the transdermal delivery of testosterone

Abstract: The objective was to develop a microemulsion formulation for the transdermal delivery of testosterone. Microemulsion formulations were prepared using oleic acid as the oil phase, Tween20 as a surfactant, Transcutol as cosurfactant, and water. The microemulsions were characterized visually, with the polarizing microscope, and by dynamic light scattering. In addition, the pH, conductivity (sigma) and viscosity (eta) of the formulations were measured. Moreover, differential scanning calorimetry and diffusion-orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
91
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(97 citation statements)
references
References 56 publications
4
91
0
2
Order By: Relevance
“…Colloidal formulations have also been shown to enhance transdermal skin penetration. [54][55][56] Results presented here demonstrate that delivery of macromolecules can be effectively achieved without the use of any specific delivery devices or the need to design complex formulations.…”
Section: Discussionmentioning
confidence: 98%
“…Colloidal formulations have also been shown to enhance transdermal skin penetration. [54][55][56] Results presented here demonstrate that delivery of macromolecules can be effectively achieved without the use of any specific delivery devices or the need to design complex formulations.…”
Section: Discussionmentioning
confidence: 98%
“…The use of microemulsions as a carrier vehicle in the topical formulations of drugs has been shown to improve the permeability of such formulations (Dantas et al, 2010;Hathout, Woodman, Mansour, 2010;Jadhav, Shetye, Kadam, 2010;Rogerio Dora, Andrade, 2010;Tsai et al, 2010). Bolzinger et al (2008) showed that microemulsions based on caffeine have better permeation than pharmaceutical forms, such as emulsion and gel.…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%
“…Sodium naproxen (Escobar-Chavez et al, 2005); Sodium diclofenac (Escribano et al, 2003); Lidocaine (Cazares-Delgadillo et al, 2005); Testosterone (Hathout et al, 2010); Mometasone furoate (Senyiğit et al, 2009); Ketorolac (Amrish et al, 2009). …”
Section: Azone ®mentioning
confidence: 99%